2002
DOI: 10.28945/2563
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Virtual Environments to Support Communication and Community in Internet-Based Distance Education

Abstract: Executive SummaryIn this paper we discuss the use of modern information and communication technologies for distance education (DE) purposes. We argue that current technologies and implementations do not adequately support the key concepts of communication and community that many practitioners believe to be important, particularly if modern pedagogies such as constructivism are to be supported. We propose that collaborative virtual environments (CVEs), which are computer-enabled, distributed virtual spaces or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
(11 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, compared to traditional methods, there are other significant characteristics of VR that could be leveraged for supporting education including the following (Laister, 2002;Bouras, et al 2008;Redfern et al, 2002;Seely et al 2008):  High levels of interactivity that VR allows: Since most people learn faster by "doing", the VR system provides significantly higher levels of interactivity than other computerbased systems. Similarly, since the interfaces are intuitive and easy to use, the degree of interactivity could be very beneficial.…”
Section: Why Is Virtual Learning (Vr) Superior To Traditional Methods?mentioning
confidence: 99%
“…Furthermore, compared to traditional methods, there are other significant characteristics of VR that could be leveraged for supporting education including the following (Laister, 2002;Bouras, et al 2008;Redfern et al, 2002;Seely et al 2008):  High levels of interactivity that VR allows: Since most people learn faster by "doing", the VR system provides significantly higher levels of interactivity than other computerbased systems. Similarly, since the interfaces are intuitive and easy to use, the degree of interactivity could be very beneficial.…”
Section: Why Is Virtual Learning (Vr) Superior To Traditional Methods?mentioning
confidence: 99%
“…Redfern and Naughton (2002) found that Collaborative virtual environments have the prospective to enable innovative and valuable distance teaching techniques and it should be based on the pedagogical requirements of the students' communities. Higgins (2002) agrees and highlights that E-learning will only be successful if it is based on sound educational approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing studies in online collaboration show that virtual communication patterns correspond in some fashion to real-life communication [28,29]. As in F2F communication, members of an OLC should be able to state what they think, comment on what others have said, collaborate on common statements, and share information in many forms.…”
Section: Web 20 Fosters Copsmentioning
confidence: 99%